Caractéristiques Dimensionnelles Des Principaux Organes Du Tractus Génital Mâle De Anisopteromalus Calandrae Howard (Hymenoptera: Pteromalidae) En Fonction De L’âge - Anani, Kafui Yolande Ella; Mondedji, Abla Déla; Amevoin, Komina; Bressac, Christophe; Glitho, Isabelle Adolé (European Scientific Journal, ESJ, 2018)
The reproductive capacity of the parasitoïd of cowpea bruchids Anisopteromalus calandrae Howard (Hymenoptera: Pteromalidae) male depends on the number of spermatozoa produced and spilled in the seminal vesicle. The objective of this study is to determine the dimensional characteristics of the different parts of the male genital tract of A. calandrae depending on age. Photographs of the parts of the male genital tract of the nymph and the virgin adults of 0- 1- 5- 10- and 15-day old were taken by light microscopy. The dimensional characteristics of the organs of the genital tract of A. calandrae has shown that when the surface of the testes decreases, that of the anterior portion of the seminal vesicle increases and the ratio between the width of the light and the total width of the accessory gland increases from emergence to the fifteenth day. The dimension of the testes decreases in favor of that of the seminal vesicle and the accessory gland of A. calandrae male depending on age.